Sodium and Potassium Complexes of Anionic N‐Heterocyclic Carbenes. Issue 9 (22nd March 2021) - Frosch, Jenni; Körner, Lukas; Koneczny, Marvin; Tamm, Matthias
Abstract: The reaction of 1, 3‐bis(2, 6‐diisopropylphenyl)imidazolin‐2‐ylidene (IDipp) with n ‐BuLi in the presence of sodium and potassium bis(trimethylsilyl)amide was studied, and the resulting polymeric dicarbene species were reacted with the fluoroboranes tris(pentafluorophenyl)borane, B(C6 F5 )3, and tris[3, 5‐bis(trifluoromethyl)phenyl]borane, B( m ‐XyF6 )3 to produce sodium and potassium salts of an anionic N‐heterocyclic carbene with a weakly coordinating borate moiety (WCA‐NHC). Abstract :